2020
DOI: 10.7759/cureus.8014
|View full text |Cite
|
Sign up to set email alerts
|

Calciphylaxis in the Setting of Hemodialysis, Liver Cirrhosis, and Warfarin Therapy for Atrial Fibrillation: An Argument for Alternative Anti-Embolic Therapy

Abstract: Calciphylaxis, also referred to as calcific uremic arteriolopathy, is a rare, life-threatening cutaneous systemic disease that typically occurs in the setting of end-stage renal disease (ESRD). ESRD is the most recognized risk factor for calciphylaxis but it is not the sole risk factor. Calciphylaxis has also been associated with liver cirrhosis with or without concurrent renal disease. The current case describes a patient who developed calciphylaxis in the setting of hemodialysis, liver cirrhosis, and atrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The transition from peritoneal dialysis to hemodialysis and the use of intensive hemodialysis is recommended as this may advance wound healing through better control of mineral metabolism. 19 Dialysis vintage before CUA diagnosis was 895 days in keeping with other studies which have ranged from 621 to 3225 days. 1,7,13,14 Being overweight or obese and having diabetes are also common risk factors identified in our and previous studies.…”
Section: Discussionsupporting
confidence: 83%
“…The transition from peritoneal dialysis to hemodialysis and the use of intensive hemodialysis is recommended as this may advance wound healing through better control of mineral metabolism. 19 Dialysis vintage before CUA diagnosis was 895 days in keeping with other studies which have ranged from 621 to 3225 days. 1,7,13,14 Being overweight or obese and having diabetes are also common risk factors identified in our and previous studies.…”
Section: Discussionsupporting
confidence: 83%
“…It occurs when vascular calcinosis causes ischemia and necrosis of the skin, subcutaneous fat, and other organs. 8 , 9 Studies have shown that 40% to 80% of adults on maintenance dialysis have soft tissue calcinosis and has an incidence of 0.5% to 3%. 10 - 12 The calcification of internal visceral organs is clinically more insidious and rarely recognized before death.…”
Section: Discussionmentioning
confidence: 99%